2020
DOI: 10.1021/acs.jpclett.0c00269
|View full text |Cite
|
Sign up to set email alerts
|

Neutral Organic Radical Formation by Chemisorption on Metal Surfaces

Abstract: Organic radical monolayers (r-MLs) bonded to metal surfaces are potential materials for the development of molecular (spin)electronics. Typically, stable radicals bearing surface anchoring groups are used to generate r-MLs. Following a recent theoretical proposal based on a model system, we report the first experimental realization of a metal surface-induced r-ML, where a rationally chosen closed-shell precursor 3,5-dichloro-4-[bis(2,4,6-trichlorophenyl)methylen]cyclohexa-2,5-dien-1one (1) transforms into a st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 51 publications
0
18
0
Order By: Relevance
“…This result is in agreement with other studies which have reported spin polarization (open‐shell character) of quinoidal derivatives by means of N‐doping, [ 47–49 ] electrochemical reduction, [ 50 ] and surface chemisorption. [ 51 ] The magnetic coupling between the spin‐polarized quinone units is rather weak both along the x and y directions, as shown with the nearly energetic degeneracy between the ferromagnetic solution with other antiferromagnetic spin configurations (see Figure S5, Supporting Information). This is typical for paramagnetic ground states, however, in such situations, the application of moderate magnetic fields, as regularly done for graphene, [ 52 ] may easily populate the ferromagnetic state of the material (Figure 4b), which is the most promising one for spintronic applications.…”
Section: Resultsmentioning
confidence: 99%
“…This result is in agreement with other studies which have reported spin polarization (open‐shell character) of quinoidal derivatives by means of N‐doping, [ 47–49 ] electrochemical reduction, [ 50 ] and surface chemisorption. [ 51 ] The magnetic coupling between the spin‐polarized quinone units is rather weak both along the x and y directions, as shown with the nearly energetic degeneracy between the ferromagnetic solution with other antiferromagnetic spin configurations (see Figure S5, Supporting Information). This is typical for paramagnetic ground states, however, in such situations, the application of moderate magnetic fields, as regularly done for graphene, [ 52 ] may easily populate the ferromagnetic state of the material (Figure 4b), which is the most promising one for spintronic applications.…”
Section: Resultsmentioning
confidence: 99%
“…Functionalization of flat surfaces [1][2][3][4][5][6][7][8][9], polymers [10][11][12][13][14], well-defined macromolecules (dendrimers [15][16][17][18], cyclodextrins [19][20][21][22], fullerene [23], and nanotubes [24]), and nanoparticles [25][26][27][28][29][30] with stable radicals is becoming an important avenue for obtaining materials [31,32] for advanced technologies [33], which include organic electronics [11,34], spintronics [1, 3,6], contrast agents in bioimaging [15,35,36], and energy storage [12,[37][38][39]. This effort has concentrated mainly on the traditional stable radicals, such as nitroxides [6,[14][15][16]…”
Section: Introductionmentioning
confidence: 99%
“…22 Recently, a switchable spinterface was realized by controllable chemisorbed and physisorbed states of organic molecules on ferromagnetic metal surfaces. 23,24 With the help of spin-resolved PES, the spin-dependent hybrid interface states at the spinterface can be directly detected and characterized in the frame of the energy-level alignment. 13,16,25,26 Rubrene is a π-conjugated molecular semiconductor possessing high carrier mobility (∼20 cm 2 /V•s).…”
Section: ■ Introductionmentioning
confidence: 99%
“…For example, a high spin injection efficiency for hot electrons and a spin diffusion length as long as 12.6 ± 3.4 nm at the CuPc/Co(001) interface were determined by spin-resolved two-photon photoemission spectroscopy (2PPE) . Recently, a switchable spinterface was realized by controllable chemisorbed and physisorbed states of organic molecules on ferromagnetic metal surfaces. , With the help of spin-resolved PES, the spin-dependent hybrid interface states at the spinterface can be directly detected and characterized in the frame of the energy-level alignment. ,,, …”
Section: Introductionmentioning
confidence: 99%